2008
DOI: 10.2337/db08-0404
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Fetal Size Is Associated With β-Cell Hyperfunction in Early Life and Failure With Age

Abstract: OBJECTIVE— Low birth weight is associated with diabetes in adult life. Accelerated or “catch-up” postnatal growth in response to small birth size is thought to presage disease years later. Whether adult disease is caused by intrauterine β-cell–specific programming or by altered metabolism associated with catch-up growth is unknown. RESEARCH DESIGN AND METHODS— We generated a new model of intrauterine growth restriction due to fatty acid synthase (FAS) haploinsufficiency (FAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…Our study demonstrates that the association of BMI z-score with low HOMA%S and high HOMA%b may correspond to an increase of HOMA%b which compensates for the low HOMA% S. Previous studies have reported that the effect of BMI on insulin resistance is more consistent and of higher effect size than BW [10,14], as also shown in our study. Results from a study using an animal model have shown that decreased fetal size is associated with beta-cell hyperfunction in early life, which is consistent with our findings [13]. It is expected that as these cohorts become older, the compensatory increase in HOMA%b will probably decrease [13].…”
Section: Interpretation Of the Findingssupporting
confidence: 90%
See 2 more Smart Citations
“…Our study demonstrates that the association of BMI z-score with low HOMA%S and high HOMA%b may correspond to an increase of HOMA%b which compensates for the low HOMA% S. Previous studies have reported that the effect of BMI on insulin resistance is more consistent and of higher effect size than BW [10,14], as also shown in our study. Results from a study using an animal model have shown that decreased fetal size is associated with beta-cell hyperfunction in early life, which is consistent with our findings [13]. It is expected that as these cohorts become older, the compensatory increase in HOMA%b will probably decrease [13].…”
Section: Interpretation Of the Findingssupporting
confidence: 90%
“…Results from a study using an animal model have shown that decreased fetal size is associated with beta-cell hyperfunction in early life, which is consistent with our findings [13]. It is expected that as these cohorts become older, the compensatory increase in HOMA%b will probably decrease [13]. Thus low HOMA%b could be an early warning of diabetes mellitus in a not too distant future in our population of young adults.…”
Section: Interpretation Of the Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…Beta cell expansion beginning in intrauterine life is independent of glucose, Insulin and Insulin receptors. [6] …”
Section: Resultsmentioning
confidence: 99%
“…In low birth weight neonates in humans as well as in rat models, hyperinsulinemia is found at very early stage. [6] 2. Development of insulin resistance is preceded by hyperinsulinemia in mice, rats as well as in humans.…”
Section: Resultsmentioning
confidence: 99%